ASPECTS OF THE PRAGMATIC UNDERSTANDING OF THE APHORISMS (Scientific journal of the Fergana State University, 2023)
In modern linguistics, more and more attention is paid to the study of aphorism as a phrasal text and a stable phrase. In this regard, it is especially relevant to analyze the properties of an aphorism that characterize it in various types of discourse and spheres of speech communication. The article presents an attempt to differentiate and describe various empirical understandings of the aphorism.